2019
DOI: 10.1039/c9cy01753d
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of surface heterogeneity of cobalt nanoparticles on the kinetics of CO methanation

Abstract: The CO hydrogenation reaction was studied under methanation conditions (H2/CO >3, 250–300 °C) on Co/SiO2 catalysts with different mean Co nanoparticle size (dp = 4 nm, 13 nm and 33 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…32,33 Recently, enhanced catalytic activity was reported for cobalt nanoparticles associated with high surface heterogeneity in terms of size and distribution. 34 The electrocatalytic activity for OER is usually measured based on the overpotential required to reach a current density of 10 mA/cm 2 with respect to the standard reaction potential of OER (1.23 V with respect to (wrt) RHE). 35,36 In our studies, the overpotential required to reach the current density is found to be 350 mV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Recently, enhanced catalytic activity was reported for cobalt nanoparticles associated with high surface heterogeneity in terms of size and distribution. 34 The electrocatalytic activity for OER is usually measured based on the overpotential required to reach a current density of 10 mA/cm 2 with respect to the standard reaction potential of OER (1.23 V with respect to (wrt) RHE). 35,36 In our studies, the overpotential required to reach the current density is found to be 350 mV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The differences in catalytic activities may be attributed to the dense and uniform deposition in the case of CoNPs prepared in the neat maline medium unlike that of CoNP AqMal /GS, as shown in Figure . The distinct morphology and scattered distribution of the relatively thin CoNP AqMal clusters (vs CoNP Mal ) favor the exposure of a large number of catalytically active edges, which contributes toward superior catalytic activity. , Recently, enhanced catalytic activity was reported for cobalt nanoparticles associated with high surface heterogeneity in terms of size and distribution …”
Section: Results and Discussionmentioning
confidence: 99%
“…3), which should in principle arise from the catalytic decomposition of carboxylic anhydrides [37], with the concomitant formation of methane. The formation of methane in this temperature range should be associated to the CO methanation activity of the cobalt phase, which also produces water [38,39]. From ICP analyses.…”
Section: Cobalt Particle Size Confinement Crystallographic Phase and Compositionmentioning
confidence: 98%
“…The fact that the co-precipitated Co 0.1 Ce 0.9 O x catalysts have higher apparent activation energies than the impregnated Co/CeO 2 catalysts seems to be related to the H 2 -TPR results that the co-precipitation method can provide a stronger interaction between cobalt oxides and ceria than the wet impregnation method. Castillo et al [64] reported that the CO consumption turnover rate was significantly lower for smaller cobalt nanoparticles during CO methanation over Co/SiO 2 catalysts with different cobalt particle sizes ranging from 4 to 33 nm. The apparent activation energy was lower for smaller cobalt nanoparticles.…”
Section: Co2 Methanationmentioning
confidence: 99%